Особливості впливу неметалевих включень на механічні властивості та малоциклову довговічність сталевих канатів при експлуатації в агресивних середовищах - Губенко, С.І.; Парусов, Е.В.; Парусов, О.В.; Чуйко, І.М. (Physico-technological Institute of Metals and Alloys, 2023)
The influence of non-metallic inclusions on the mechanical properties and low-cycle durability of steel C72D (EN 161202:2011) in corrosive environments has been established. A consistent decreasing series of non-metallic inclusions is established and substantiated, which characterizes the degree of their harmful influence on the nucleation and development of corrosion damage to the wires of the outer layer of steel ropes made of steel C72D. The most harmful effect of sulphide and heterophase inclusions on the nucleation and development of corrosion damage during the operation of steel ropes cables in various environments has been substantiated.